3+5(-8a-1)=-6-(3a-4)

Simple and best practice solution for 3+5(-8a-1)=-6-(3a-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+5(-8a-1)=-6-(3a-4) equation:


Simplifying
3 + 5(-8a + -1) = -6 + -1(3a + -4)

Reorder the terms:
3 + 5(-1 + -8a) = -6 + -1(3a + -4)
3 + (-1 * 5 + -8a * 5) = -6 + -1(3a + -4)
3 + (-5 + -40a) = -6 + -1(3a + -4)

Combine like terms: 3 + -5 = -2
-2 + -40a = -6 + -1(3a + -4)

Reorder the terms:
-2 + -40a = -6 + -1(-4 + 3a)
-2 + -40a = -6 + (-4 * -1 + 3a * -1)
-2 + -40a = -6 + (4 + -3a)

Combine like terms: -6 + 4 = -2
-2 + -40a = -2 + -3a

Add '2' to each side of the equation.
-2 + 2 + -40a = -2 + 2 + -3a

Combine like terms: -2 + 2 = 0
0 + -40a = -2 + 2 + -3a
-40a = -2 + 2 + -3a

Combine like terms: -2 + 2 = 0
-40a = 0 + -3a
-40a = -3a

Solving
-40a = -3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3a' to each side of the equation.
-40a + 3a = -3a + 3a

Combine like terms: -40a + 3a = -37a
-37a = -3a + 3a

Combine like terms: -3a + 3a = 0
-37a = 0

Divide each side by '-37'.
a = 0

Simplifying
a = 0

See similar equations:

| 0.15-0.01(x+1)=-0.03(2-x) | | (-2x/11)=66 | | 7x+3=2(3x+1)-x+8 | | x+6=15-x | | 13/6+x=6 | | 16n^2-8n-15=0 | | 2x-5y=4x+15 | | 5/2x=3/2x-4 | | 35x^4-2x^2-1=0 | | 14w-18=94 | | 9(x+6)+5=59 | | -533-(-276)= | | -2(-6k-5)=-15+7k | | -x+3+11x=-3+4x+48 | | .5x+.05x=256 | | 4(5k-5)+19=-9+2(3k-8) | | 13+3(2x-5)=1-2(3-6x) | | 3c-1c+40=34 | | 4/3+2=6 | | x+2x+13=70 | | 7.5-(-2.5)= | | a(c-2)+3(c-2)= | | 92=-8+25m | | x+.05x=23.63 | | -(5+2x)=2(3+4x) | | 5t-14=8t+4 | | 3(n-5)=9-n | | 2x+4=-1(7x+6) | | 1(5+2x)=2(3+4x) | | 8y-8=64 | | 5y/6-23=7 | | 350x23/20x7/25 |

Equations solver categories